A multicomponent workplace environmental intervention to promote physical activity among the staff of universiti Malaysia Sarawak - Yong Xiang Cheah; Whye Lian Cheah; Helmy Hazmi (Wolters Kluwer Medknow Publications, 2024)
Background: Physical inactivity is a significant public health issue affecting working adults because it can increase the risk of noncommunicable diseases. Objectives: The objective is to determine the outcomes of a multi-component workplace environmental intervention that incorporated physical activity self-regulation (PASR) to promote physical activity (PA) among employees. Materials and Methods: This was a 6-month intervention with a two-group, parallel, quasi-experimental study. A total of 11 workplaces were randomly assigned to intervention group (IG) or control group (CG) using a 1:1 allocation ratio. In each group, 84 eligible participants were recruited. The IG was exposed to the organizational support and the PA support components throughout the study. The PASR Scale, International PA Questionnaire, and pedometer were used to measure the outcome at the baseline, 3rd-month, and 6th-month follow-ups, respectively. The repeated measures-analysis of variance analysis was used to determine the changes in the PASR skills, MET-min/week, and step/week over time. Results: The IG had 75 participants (51 females and 24 males) and the CG had 73 participants (52 females and 21 males) at the 6th-month follow-up. Despite there was no statistically significant difference in the outcomes between groups over time, the IG showed significant improvements in total PASR (ηp2 = 0.021), goal setting (ηp2 = 0.024), total MET-min/week (ηp2 = 0.031), housework-related PA (ηp2 = 0.101), and step/week (ηp2 = 0.827) throughout this intervention. Conclusion: This intervention was found to be effective in improving the PASR skills, MET-min/week, and step/week of IG participants. Meanwhile, because some effect sizes were small, these findings should be interpreted with caution.